Influence of innovative methods of fitness training on improvement of technical fitness of qualified gymnasts in aerobic gymnastics - Kokarev, B.; Kokareva, S.; Putrov, S.; Artemieva, H. P.; Verbytsyi, S. (Journal of Physical Education and Sport, 2023)
Purpose Nowadays it is impossible to imagine the training process of highly qualified athletes in various kinds of professional and Olympic sports without the use of innovative fitness technologies with appropriate equipment, tools and techniques. In particular, they are widely used in the educational and training process of gymnasts to improve certain aspects of their physical, functional and technical preparedness. The purpose of this study is to substantiate the feasibility of using innovative tools, methods and related techniques borrowed from health fitness aerobics to improve the technical preparedness of highly skilled athletes in aerobic gymnastics.